Variation in Milk Yield Of Dairy Cattle: Evaluation on Correction Factors of Internal Environmental Effects - Anneke Anggraeni (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Correction factors as standard factor are needed to standardize internal environmental effects to evaluate genetic for desired traits of each breed, strain, or individual animal. Some dairy cattle scientists in warm (cold) and hot climate have made observing correction factors (CF) of internal environmental effects mainly for stages (days length) of lactation, calving age, milking ftequency, days open, and dry period for milk and its components (protein and fat). The correction factors should be done due to high variability on  those parameters that occur natually eventhough dairy management have been kept well. Developing correction factors of calving age, days open, and days dry for milk production becomes main discussion in this paper. In Indonesia, correction factors of internal environmental effect for local Fries Holland dairy cattle need to be developed. The appropriate correction factors will be effective to eliminate the variation of milk yield caused by non-genetic effects. So the result of evaluation and selection could be expected to figure out genetic potencial of dairy cattle in producing milk.   Key words: Milk yield, correction factors, and internal environment